Minimally Invasive Revisional Bariatric Surgery in a MBSAQIP Accredited High-Volume Center - Xie, Julia; Dreifuss, Nicolas H.; Schlottmann, Francisco; Cubisino, Antonio; Mangano, Alberto; Vanetta, Carolina; Baz, Carolina; Valle, Valentina; Bianco, Francesco M.; Gangemi, Antonio; Masrur, Mario A. (Frontiers in Surgery, 2022)
Background: With the rising number of bariatric surgeries performed annually, there has also been an increase in revisional bariatric surgeries (RBS). The aim of this study is to evaluate the safety and postoperative outcomes of RBS performed with a minimally invasive approach. Methods: Retrospective analysis on a prospectively collected database of patients who underwent minimally invasive RBS between 2012 and 2019. Primary endpoints were conversion rate, major morbidity, mortality, and 30-day reoperation rate. Comparative analysis of laparoscopic adjustable gastric banding (LAGB) conversion to sleeve gastrectomy (SG) versus conversion to Roux-en-Y gastric bypass (RYGB) was performed. Results: A total of 221 patients underwent minimally invasive RBS, 137 (62%) laparoscopically and 84 (38%) robotically. The most common RBS were LAGB to SG (59.3%) and LAGB to RYGB conversions (16.7%). The main indication was weight loss failure (88.7%). Conversion rate, major morbidity, and mortality were 0.9%, 3.2%, and 0.4%, respectively. Urgent reoperation was required in 3.2% of cases. Total weight loss at 1 and 2-years follow- were 14.3% and 17.3%, respectively. Comparative analysis of LAGB conversion to SG versus RYGB showed similar major morbidity (SG: 2.3% vs. RYGB 0%, p=1). Greater total weight loss was achieved in LAGB to RYGB conversions at 1-year (SG: 14.8% vs. RYGB 25.3%, p<0.001). Conclusions: Minimally invasive RBS can be performed safely in a broad patient population with low conversion and complication rates, and improved weight loss outcomes. LAGB to RYGB conversions are associated with greater weight loss. Further randomized trials are needed to draw more conclusive recommendations.